1996
DOI: 10.1136/sti.72.3.220
|View full text |Cite
|
Sign up to set email alerts
|

Why do men with urethritis in Cameroon prefer to seek care in the informal health sector?

Abstract: Objective: To study the impact of cost of treatment for sexually transmitted diseases (STDs) on the preference of men with urethritis to seek care in the informal sector. Subjects and methods: A random sample of young men from the general population of Yaounde and Douala, Cameroon, and of employees of a Yaounde factory underwent a structured interview on the occurrence of STD-related complaints and health seeking behaviour. Men who consulted in the formal sector were compared with men consulting in the informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 4 publications
1
23
0
Order By: Relevance
“…29 Promotion of appropriate treatment seeking behaviour and the role of the private sector Surveys of health seeking behaviour in developing countries indicate that a substantial proportion of people with symptomatic STIs seek treatment in the informal or private sector, from traditional healers, unqualified practitioners, street drug vendors, and from pharmacists and private practitioners, and they will only attend formal public health services after alternative treatments have failed. 30 Self medication is also popular in many settings. [30][31][32] Patients seek care in the private sector for many reasons, including their greater accessibility and convenience, and the more confidential, less judgmental, and less stigmatising nature of the services.…”
Section: Screening and Case Findingmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Promotion of appropriate treatment seeking behaviour and the role of the private sector Surveys of health seeking behaviour in developing countries indicate that a substantial proportion of people with symptomatic STIs seek treatment in the informal or private sector, from traditional healers, unqualified practitioners, street drug vendors, and from pharmacists and private practitioners, and they will only attend formal public health services after alternative treatments have failed. 30 Self medication is also popular in many settings. [30][31][32] Patients seek care in the private sector for many reasons, including their greater accessibility and convenience, and the more confidential, less judgmental, and less stigmatising nature of the services.…”
Section: Screening and Case Findingmentioning
confidence: 99%
“…30 Self medication is also popular in many settings. [30][31][32] Patients seek care in the private sector for many reasons, including their greater accessibility and convenience, and the more confidential, less judgmental, and less stigmatising nature of the services.…”
Section: Screening and Case Findingmentioning
confidence: 99%
“…Research in Kenya (M oses et al, 1992), as well as in Cameroon (Crabbe et al, 1996), showed the high cost of treatment was a deterrent to the use of the public clinics. In studies from Zambia (Sajiwandani et al, 1987) and Swaziland (Green, 1992), shame and embarrassment inhibited persons from seeking care, particularly at public clinics.…”
Section: Discussionmentioning
confidence: 97%
“…Other consequences mentioned included`PID' (8),`damage to the fallopian tubes' (7),`ectopic pregnancy' (6), and`affecting newborns' (6). The main sources of information on the treatment of STD were professional training (11), in-service training (4) and DoSH guidelines (3).…”
Section: Knowledge and Attitudesmentioning
confidence: 99%
“…Surveys of health-seeking behaviour in developing countries indicate that a substantial proportion of people with symptomatic STDs seek treatment in the informal or private sector from traditional healers, unquali® ed practitioners, street drug vendors, and from pharmacists and private practitioners 3± 7 , and will only attend formal public health services after alternative treatments have failed 8 . There are, however, indications that the management of STD patients in the informal or private sector is less than optimal, as allopathic practitioners may not use adequate drugs or suitable drug regimens, or may not provide proper education and counselling 7,9± 11 , whilst traditional healers and herbalists may use remedies with no proven antimicrobial ef® cacy 6 .…”
Section: Introductionmentioning
confidence: 99%